Influence of Grid Economic Factors on Scheduling and Migration - Moreno-Vozmediano, Rafael; Alonso-Conde, Ana B. (High Performance Computing for Computational Science - VECPAR 2004, 2005)
Grid resource brokers need to provide adaptive scheduling and migration mechanisms to handle different user requirements and changing grid conditions, in terms of resource availability, performance degradation, and resource cost. However, most of the resource brokers dealing with job migration do not allow for economic information about the cost of the grid resources. In this work, we have adapted the scheduling and migration policies of our resource broker to deal with different user optimization criteria (time or cost), and different user constraints (deadline and budget). The application benchmark used in this work has been taken from the finance field, in particular a Monte Carlo simulation for computing the value-at-risk of a financial portfolio.